1990
DOI: 10.1007/bf00197110
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular deamination of l-amino acids by Chlamydomonas reinhardtii cells

Abstract: When grown in the light and in a Tris-acetate phosphate medium, cells of Chlamydomonas reinhardtii Dang. can use the following L-amino acids as a sole nitrogen source: asparagine, glutamine, arginine, lysine, alanine, valine, leucine, isoleucine, serine, methionine, histidine, and phenylalanine, whereas, in the absence of acetate, the cells only used L-arginine. The utilization system in the acetate medium consisted of an extracellular deaminating activity induced by L-amino acids; it took between 10 to 30 h b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 23 publications
2
45
0
2
Order By: Relevance
“…In addition, ARF1 cells did not consume MSX nor did keto acids appear when ammonium was present together with MSX in the growth medium. Since LAO expression is repressed by ammonium (MunÄ oz- Blanco et al 1990), this ®nding is consistent with LAO being the major activity responsible for MSX utilization in ARF1.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In addition, ARF1 cells did not consume MSX nor did keto acids appear when ammonium was present together with MSX in the growth medium. Since LAO expression is repressed by ammonium (MunÄ oz- Blanco et al 1990), this ®nding is consistent with LAO being the major activity responsible for MSX utilization in ARF1.…”
Section: Resultssupporting
confidence: 77%
“…However, this point remains controversial, since other evidence indicates that other amino acids, such as leucine, proline and methionine, could also be taken up by this alga (discussed in Harris 1989). In addition, it has been reported that growth with amino acids in C. reinhardtii can only be supported through their deamination by LAO activity (MunÄ oz-Blanco et al 1990). This enzyme has been puri®ed from C. reinhardtii (Piedras et al 1992;Vallon et al 1993), and a cDNA for its catalytic subunit cloned and sequenced (Vallon and Wollman 1997).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The e-amino-acid oxidase of C. reinhardtii was able to deaminate nonspecifically 12 L-amino acids but at different rates (Mufioz-Blanco et al 1990). The apparent Km values of those twelve amino acids have been determined for the oxidase reaction and ranged between 31 laM for phenylalanine and 176 I~M for methionine, thus confirming the nonspecificity towards its substrates of this cell-surface oxidase.…”
Section: Resultsmentioning
confidence: 98%
“…В частности, было показано, что при выращи-вании на свету и с добавлением трис-ацетатфосфата в питательную среду клетки Ch. reinhardtii CC-124 используют следующие L-амино-кислоты в качестве единственного источника азота: аспарагин, глутамин, аргинин, лизин, аланин, валин, лейцин, изолейцин, серин, метионин, гистидин и фенилаланин, тогда как при отсутствии ацетата, клетки используют только L-аргинин (Muсoz-Blanco et al, 1990). При миксотрофном культивировании Ch.…”
Section: результаты и обсуждениеunclassified